Design of an integrated warehouse management system at Politeknik Astra using the scrum method - Danang Adi Kuncoro; Rifdah Zahabiyah; Rohmat Setiawan; Noviani Putri Sugihartanti; Muhammad Izzat Ibaddurahman (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
This study addresses the problem of fragmented, manual, and low-visibility warehouse management in the Technical Service Units (UPT) at Politeknik Astra, which has led to operational inefficiencies and the emergence of dead stock. The objective of this research is to design and implement an integrated Warehouse Management System (WMS) to improve inventory transparency, data accuracy, and operational efficiency. The system was developed using the Scrum methodology through five iterative sprints, each lasting two weeks, involving requirement analysis, system design, implementation, and evaluation. Functional and non-functional testing is performed using Black-box Testing, Integration Testing, and User Acceptance Testing. The results indicate that the developed WMS successfully integrates purchasing requests, goods receiving, picking, borrowing, stock monitoring, and reporting processes into a standardized and real-time system. The system improves inventory visibility, reduces recording errors and duplicate purchasing, and supports faster and more accurate operational decision-making. In addition, the implementation of the WMS generates measurable financial benefits through cost savings in system procurement, training, materials, and warehouse space utilization. This study demonstrates that an integrated WMS developed using Scrum can effectively enhance warehouse management performance in vocational education institutions